France and European integration : towards a transnational polity? - Gueldry, Michel R. (Praeger, 2001)
This title analyzes the substantive transformations brought upon the French state by European integration through an incremental and cumulative process generally described as ""Europeanization"". It also examines how regional integration affects French governmental structures.